2015
DOI: 10.1021/acs.jafc.5b00605
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Conditioning Alleviates Chilling Injury in Loquat Fruit and Regulates Glycine Betaine Content and Energy Status

Abstract: The influence of low-temperature conditioning (LTC) treatment on chilling injury, glycine betaine content, and energy metabolism in loquat fruit at 1 °C storage was investigated. The results indicated that LTC treatment significantly reduced chilling injury index, ion leakage, and malondialdehyde content in loquat fruit. Betaine aldehyde hydrogenase (BADH) activity and endogenous glycine betaine (GB) content in loquats treated with LTC were significantly higher than those in control fruit. Moreover, LTC treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…In the current study, higher SDH and CCO activities were observed in GB-treated papaya fruit during cold storage when compared to untreated fruit, implying that GB could induce the increase in activity of key mitochondria enzymes involved in energy metabolism, thus contributing to elevated energy status and improved chilling tolerance. Similar results were also reported in MeJA-treated peaches (Jin et al, 2013), H 2 S-treated bananas , and LTC-treated loquats (Jin et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the current study, higher SDH and CCO activities were observed in GB-treated papaya fruit during cold storage when compared to untreated fruit, implying that GB could induce the increase in activity of key mitochondria enzymes involved in energy metabolism, thus contributing to elevated energy status and improved chilling tolerance. Similar results were also reported in MeJA-treated peaches (Jin et al, 2013), H 2 S-treated bananas , and LTC-treated loquats (Jin et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, higher activities of H + -ATPase and Ca 2+ -ATPase in parallel with alleviated CI were observed in GB-treated papayas during low temperature storage, indicating that GB-induced chilling tolerance might be related with enhancement of both ATPases activity. Similar results were also observed in methyl jasmonate (MeJA)-treated peaches (Jin et al, 2013), NO-and H 2 S-treated bananas Wang et al, 2015), 1-methylcyclopropene-treated pears (Cheng et al, 2015), and low temperature conditioned (LTC)-loquats (Jin et al, 2015). These findings indicate that both H + -ATPase and Ca 2+ -ATPase in harvested crops could be favorable for affording tolerance to chilling stress by sustaining membrane energization .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Low temperature conditioning is one of most effective means of alleviating CI in diverse fruits, such as zucchini and squash (Wang ), avocado (Hofman et al ), loquat (Cai et al ; Wang et al ) and grapefruit (Chaudhary et al ), where the effects depend on a combination of conditioning temperature and duration, with effective combinations varying with species and cultivars. For example, 5–10 °C for 6 d before 0 °C storage for loquat (Cai et al ; Jin et al ), 16 °C for 7 d before 2 °C cold storage for mandarin (Sapitnitskaya et al ) and grapefruit (Chaudhary et al ) have been reported as effective. For peach, Jin et al () found that 10 °C for 2 d prior to 0 °C led to alleviation of CI in ‘Baifeng’ peach fruit.…”
Section: Introductionmentioning
confidence: 99%
“…cv. ''Jiefangzhong'') fruit is an important cultivar in the Chinese market, and is sensitive to chilling stress (Jin et al 2015). Fresh ripe fruits were harvested at commercial maturity from an orchard in Fujian, China ( Fig.…”
Section: Fruit Materials and Treatmentmentioning
confidence: 99%